The forgotten sisters - Hale, Shannon (Hale, Shannon. Princess Academy (Series), 2015)
Miri's eager to return to her beloved Mount Eskel after a year at the capital, but the king and queen ask her to first journey to a distant swamp and start her own miniature princess academy for three royal cousins, but once there she must solve a mystery before she can return home.